Parasitism, sex ratio, developmental time and gregariousness of Acerophagus papayae (Hymenoptera: encyrtidae) on male and female host stages of Paracoccus marginatus in no-choice situations - Mastoi, Muhammad Ishaque; Adam, Nur Azura; Muhamad Awang, Rita; Abd Ghani, Idris; Ibrahim, Yusof (Federal Urdu University of Arts, Science and Technology, 2014)
Acerophagus papayae, accidentally introduced parasitoid of Paracoccus marginatusin Malaysia was studied for parasitism, sex ratio, developmental time and gregariousness behaviour. The parasitoid was able to develop in all stages of P. Marginatus except first instars, prepupaand pupa. The maximum parasitism (59.0±5.66%) was observed in second instar female nymph and minimum (39.0±3.48%) in adult female P. marginatus. In adult female, the A. Papayae showed gregariousness behaviour (2.87 individuals per host). Male biased sex ratio (69.14 ± 3.37%) was observed in second instar male and female biased sex ratio (71.76± 4.21% and 71.53 ± 4.33%) was observed in third instar female nymph and adult female P. Marginatus respectively. The minimum and maximum developmental time for male A. papayae(13.00 and 13.89 days) was found in second instar female nymph and adult female P. Marginatus respectively. However, minimum and maximum developmental time for female A. papayae(13.85 and 14.42 days) was found in second instar male nymph and third instar female nymph of P. marginatus. The parasitoid showed gregarious behaviour (2.87 individuals per host) only in adult female P. marginatus. This vital information can be used in evaluating the efficiency of parasitoid.